Risk Management Practices in Nigeria Construction Sector and Impact on Project Performance - Oyekunle, Olaitan (Journal of Science & Technology, 2024)
The construction industry in every nation is essential to the growth of the economy and its development. The industry is characterized by complex projects, unpredictable variables, and is dependent on many different stakeholders, which subject projects in this sector to a variety of risks that can have a significant impact on project delivery. Risks in construction projects in Nigeria can lead to cost overruns, schedules not being met, and low quality of the project. The concept of risk management involves the management of identified risks which reduces the likelihood of their occurrence and the consequences of adverse risks. A project may be delivered or deemed successful, but not meet the project performance objectives. The Nigerian construction industry has undergone incredible growth and progress; however, there have been numerous challenges that have prevented project performance, such as a lack of expertise, knowledge gaps, and a drought of experienced personnel. The study examines the various risk management practices and their impact on construction project performance. Project performance implies that the project objectives are met in terms of cost, schedule, and quality. A survey research method was adopted using a questionnaire as the primary instrument for data collection on a five-point Likert scale. The questionnaire was designed to collect data relating to risk management’s impact on project performance. The questionnaires were also designed to collect data on risk identification as a risk management practice and its impact on project performance. A total of 85 questionnaires were administered and analyzed. The results from the study indicate a strong relationship between risk management practices and project performance.
Keywords: Risk Management; Project Performance; Risk Identification; Risk Assessment; mitigation strategies; Construction Sector